THE POSSIBILITY OF PROVIDING THE BEST ACCOUNTING INFORMATION FOR THE USERS - Ali Qasim Al-Obaidi (Статистика и экономика, 2016)
Accounting information is used for both internal and external purposes. To be useful the accounting information must possesssome advantages that give utility andvalue to the information presented in theﬁnancial statements and help the businessorganizations to achieve its goals properly.